Implementation of Mentoring for Young Mothers in Raising Awareness of the Importance of Maintaining Reproductive Health - Choiro, Umu Dawatul; Sri Redjeki, Endang; Khotimah, Kusnul; Salsabiala, Defriska (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The current condition of women's reproductive health in Indonesia is not in accordance with reproductive health indicators. It is necessary to analyze how the implementation of mentoring provided to young mothers to maintain reproductive health at productive age. The purpose of this study is to reveal how the implementation of mentoring young mothers in raising awareness of the importance of maintaining reproductive health. This research uses a qualitative research approach with descriptive analysis. The subject of this research is the mother guardian of students from PAUD Lazuardi located in Kedungrejo, Pakis, Malang. The results showed that the implementation of this mentoring activity carried out found that there were still many mothers who had not conducted cervical breast examinations so that the implementation of mentoring began with meetings with mothers, program socialization and personal hygiene practices.